Adoption of Mobile Web Among University Students in Malaysia: A Review - Thaneshan, L; Mat Yamin, Fadhilah; Othman, Siti Norezam (UUM Press, 2017)
This paper reviews major issues of mobile technology and mobile web usage among university students, including characteristics, importance and problems faced by university students when accessing web sites through mobile devices. This article also reviews the technology adoption models/theories that will best explain the adoption of IT/IS. The author identified Technology Acceptance Model (TAM) as the best model in explaining adoption of mobile web because TAM is the most suitable in explaining behavioural intention in the context of mobile devices. Mobile Web is the World Wide Web which is accessed through a mobile device such as laptop computer, smart phone or tablet. It establishes the entirety of the Internet and is not limited to webpages which have been specifically designed to be viewed through mobile devices. Distinctive features of mobile technology especially mobile web technology and its progressive impacts on information transfer and learning process has created many educational opportunities for higher education institutions. Although mobile devices are highly flexible, accessible and convenient, students are still facing great problems when they use mobile web for educational purpose.